Hubungan Konsumsi Fast Food dan Minuman Manis dengan Risiko Obesitas pada Remaja Putri - Jessica Dwi Rahma Nauli H; Rizkan Maulana; Laurena Ginting; Vina Gabriella Saragih (Lembaga Pengembangan Kinerja Dosen, 2026)
The prevalence of obesity among adolescent girls is increasingly becoming a global health concern that demands serious attention. Modern lifestyle changes and the frequent consumption of high-calorie foods—particularly fast food and sugary beverages—are major contributors to the rising risk of obesity in this age group. This study aims to identify the relationship between the level of fast food and sugary drink consumption with the likelihood of obesity among adolescent girls. A quantitative research approach with a survey design was employed, involving 73 respondents aged 17–22 years who were selected using purposive sampling. Data were collected through a questionnaire on consumption frequency and Body Mass Index (BMI) measurements to determine nutritional status. Statistical analysis was performed using the Chi-Square test to examine correlations between variables. The results revealed a significant association between fast food consumption (p = 0.001) and sugary drink intake (p = 0.002) with obesity risk. These findings indicate that an unbalanced diet and excessive intake of high-sugar and high-fat foods contribute to weight gain. Therefore, nutritional education and the promotion of healthy eating habits among adolescents are essential to prevent obesity in the future.